PEMBELAJARAN KONSEP DASAR IPA II MODEL STAD DENGAN EKSPERIMEN DAN NON EKSPERIMEN DILENGKAPI LKM DITINJAU DARI SIKAP ILMIAH MAHASISWA - Eksan, Moh. Budi Susilo (Universitas Nusantara PGRI Kediri, 2015)
ABSTRACT: The research used experimental and non experimental. The population is the students PGSD of Nusantara PGRI University Kediri in the academic year 2013/2014, Sample is taken by claster random sampling technique, number 2 classes. The technique of collecting data from the variable of cognitive learning student’s achievement are collected by tes method and learning motivation are collected by questionnaires. The technique of analyzing data is ANAVA two ways different cell. The objectives of the research are to know: (1) the effect of STAD learning with experiment and non experiment completed by students worksheet to the student’s achievement in basic concept of science. (2) the effect of high and low Natural Attitude to the student’s achievement in basic concept of science. (3) interaction between study using STAD either experiment and non experiment completed by students worksheet is reviewed from Natural Attitude to the student’s achievement in basic concept of science. Based on the result of the research are concluded : (1) there are effect of STAD learning either experiment and non experiment completed by students worksheet to the kognitive and affective student’s achievement in basic concept of science. (2)there are effect of high and low Natural Attitude to the student’s achievement in basic concept of science (3) no interaction between learning method and Natural Attitude to the kognitive student’s achievement in basic concept of science. Keywords: STAD, Experiment students, Unexperiment students , Worksheet, Natural Attitude, and Student Achievement. ABSTRAK: Penelitian ini menggunakan metode eksperimen dan non eksperimen. Populasi adalah seluruh mahasiswa tingkat I Program Studi PGSD di Universitas Nusantara PGRI Kediri tahun ajaran 2013/2014 dengan teknik Claster random sampling sejumlah 2 kelas. Teknik pengumpulan data variabel prestasi belajar kognitif digunakan metode tes, sikap ilmiah digunakan metode angket. Metode yang digunakan pada penelitian ini adalah metode eksperimen dengan menggunakan anava dua jalan dengan rancangan faktorial 2x2. Faktor pertama adalah model pembelajaran yaitu model pembelajaran kooperatif dengan metode STAD dengan eksperimen dan non eksperimen dilengkapi Lkm.Faktor kedua adalah sikap ilmiah siswa. Data yang diperoleh dari hasil penelitian ini berupa nilai prestasi belajar menggunakan STAD eksperimen dan non eksperimen yang ditinjau dari motivasi belajar, dan sikap ilmiah siswa. Dari data diperoleh nilai P-Value metode = 0,073, sedangkan P-Value sikap ilmiah = 0,000 dan P-Value interaksi metode dan sikap ilmiah = 0,220 Berdasarkan hasil penelitian dapat disimpulkan: (1) Ada pengaruh antara pembelajaran STAD dengan Eksperimen dan Non Eksperimen dilengkapi Lkm terhadap prestasi belajar kognitif (2) Sikap ilmiah mahasiswa memberikan pengaruh yang signifikan terhadap prestasi belajar mahasiswa.(3) Tidak ada interaksi antara siswa yang diberi pembelajaran baik menggunakan STAD eksperimen maupun STAD non eksperimen dengan sikap ilmiah mahasiswa Kata Kunci : STAD, LKM, Sikap Ilmiah, Prestasi Belajar.